ON h-HOLOMORPHY AND h-ANALYTICITY OF FUNCTIONS OF AN h-COMPLEX VARIABLE - В. А. Павловский; И. Л. Васильев (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2020)
Interest in the study of the properties of functions defined on the set of h-complex numbers arose again in connection with existing applications in geometry and mechanics. In this paper, we present necessary and sufficient conditions for h-differentiability and h-holomorphy of functions of an h-complex variable, the theorem on finite increments is proved, sufficient conditions for h-analyticity are found, a uniqueness theorem for h-analytic functions is proved.